Therapeutic repetitive Transcranial Magnetic stimulation (rTMS) for neurological dysfunction in Degenerative cervical Myelopathy: An unexplored opportunity? Findings from a systematic review. (August 2021) - Gharooni, Aref-Ali; Khan, Maaz; Yang, Xiaoyu; Anwar, Fahim; Davies, Benjamin; Kotter, Mark
Highlights: DCM leads to lifelong disability, even after surgical intervention. To date, no studies have investigated neuromodulation using rTMS in DCM. Rehabilitation and novel therapies are a JLA research priority in DCM. Further research is warranted in this area. Abstract: Degenerative Cervical Myelopathy (DCM) is one of the commonest causes of non-traumatic Spinal Cord Injury (SCI) leading to significant neurological impairments and reduced health-related quality of life. Guidelines recommend surgical intervention to halt disease progression in moderate-to-severe cases, and whilst many do experience neurological recovery, this is incomplete leading to lifelong disability. A James Lind Alliance (JLA) research priority setting partnership for DCM highlighted novel therapies and rehabilitation as top 10 research priority in DCM. Neurological recovery following decompressive surgery in DCM has been attributed neuroplasticity, and therapies influencing neuroplasticity are of interest. Electrical neuromodulation interventions such as repetitive Transcranial Magnetic Stimulation (rTMS), are being increasingly explored in related fields such as spinal cord injury to improve recovery and symptoms. The aim of this systematic review was to determine the role and efficacy of rTMS as a therapeutic tool in managing neurological dysfunction in DCM. We searched the databases of Medline, EMBASE, CINAHIL and Cochrane Central Register of Controlled Trials (CENTRAL). No studies were identified that had investigated the therapeutic use of rTMS in DCM. A significant number of studies had explored TMS based neurophysiological assessments indicating its role as a screening and prognostication tool in DCM. Post-operative rehabilitation interventions including TMS and non-operative management of DCM is a field which requires further investigation, as required in the AO Spine JLA DCM research priorities. rTMS is a safe neuromodulatory intervention and may have a role in enhancing recovery in DCM. Further research in these fields are required.